Prophets and power. Micah 3:8 - a case study - Wessels, W. (Journal for semitics, 2007)
Power plays a role in all societies. This is clearly also the case in Israel and Judah. Within the societies of Israel and Judah the prophets formed part of the power structures. Prophets not only had powerful positions in the society, but were people speaking powerful words. Prophets however concerned themselves in particular with the abuse of power. In this regard Micah is a good example of a prophet confronting and addressing the issue of power abuse in his society. The book of Micah contains a clear portrayal of power abuse; but it is not only about power. It is also about powerlessness. Chapters 2 and 3, on the one hand, spell out how powerful leaders abused their power over powerless people; and Chapter 3 shows how, on the other hand, religious functionaries (prophets, priests, seers, diviners) who had lost the favour of Yahweh were powerless against a prophet empowered by the Spirit of Yahweh to exercise a forceful prophetic ministry (3:8). Then, too, power must remain within ethical bounds if it is not to degenerate into abuse of power. Micah states clearly that power must promote justice and righteousness. If it does not, it is not to the advantage of society.,